Análise molecular da prevalência dos genes beta-lactamases blactx-m, blashv e blatem em klebsiella pneumoniae isoladas de pacientes com diagnóstico de infecção hospitalar na Santa Casa de misericórdia de Sobral, Ceará. - Rocha, Francisco Ruliglésio (2015)
Klebsiella pneumoniae is a Gram-negative bacillus responsible for a significant portion of urinary tract infections, respiratory, and bloodstream of adults in hospitals, besides infections in neonates in intensive care units. Its importance has increased due the emergence of extended- spectrum beta-lactamase-producing strains (ESBLs). These enzymes mediate resistance to oxyimino-β-lactams. In K. pneumoniae, most of the identified ESBLs are of the TEM, SHV, and CTX-M types. In addition, carbapenem-hydrolyzing beta-lactamases of KPC and GES types has been detected in these isolates. Outbreaks of nosocomial infections caused by multidrug-resistant K. pneumoniae clones have been described in various regions of the country. However, this is the first report of the genetic characterization of ESBL-producing K. pneumoniae in the state of Ceará, Brazil. This study aimed firstly to detect the main genes responsible for ESBL production in K. pneumoniae strains obtained from patients who developed nosocomial infections in a tertiary support hospital in the northern region of the Ceará state, from November 2013 to August 2014 and, secondly, to analyze the genetic similarity of these isolates. Thirty-six clinical isolates of ESBL-producing K. pneumoniae were evaluated. The detection of blaCTX-M groups 1 and 2, blaSHV-like, blaTEM-like, blaKPC-like, and blaGES- like genes was performed by PCR. Molecular typing of isolates was performed by pulsed-field gel electrophoresis PFGE. Groups 1 or 2 blaCTX-M and blaSHV-like genes were detected in 100% of the isolates and blaTEM-like genes in 55.6%. In addition, 55.6% of CTX-M-producers also produced SHV and TEM. No blaKPC-like and blaGES-like genes were detected. Molecular typing by PFGE showed great diversity between the isolates, although two isolates collected in different wards showed the same banding profile and had the same bla genes and so were considered to belong to a single strain. Detection of blaCTX-M genes in 100% of the isolates suggests that CTX-M enzymes are the major ESBLs responsible for the beta-lactam resistance phenotypes of the studied isolates. Data presented in this study call attention to an endemic resistance problem caused by multiclonal strains of multidrug-resistant K. pneumoniae whose control passes essentially the improvement of antimicrobial prescription policies and the implementation of prevention and control programs the spread of these pathogens in the studied hospital.